2018
DOI: 10.1039/c8dt01451e
|View full text |Cite
|
Sign up to set email alerts
|

Diborane heterolysis: breaking and making B–B bonds at magnesium

Abstract: Reactions of β-diketiminato magnesium diboronate complexes with 4-dimethylaminopyridine or diborane reagents provide terminal boryl or triborane anions, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 56 publications
0
33
0
1
Order By: Relevance
“…Our own research has focused on b-diketiminato (BDI) magnesium compounds such as [(BDI)Mg{pinBB(n-Bu)pin}] (9, Scheme 1). 45,46 The [pinBB(n-Bu)pin] À diboranate anion is analogous to that of species 8 and we have observed that compound 9 reacts similarly through elimination of n-BuBpin and as a reagent for nucleophilic B-C and B-B bond formation when treated with C-or B-centred electrophiles. [47][48][49] Although this is consistent with the generation of an intermediate boryl species, we have also observed that reaction of 9 with imines provides the N-B bonded organomagnesium compounds rather than the product of nucleophilic C-borylation (Scheme 1).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Our own research has focused on b-diketiminato (BDI) magnesium compounds such as [(BDI)Mg{pinBB(n-Bu)pin}] (9, Scheme 1). 45,46 The [pinBB(n-Bu)pin] À diboranate anion is analogous to that of species 8 and we have observed that compound 9 reacts similarly through elimination of n-BuBpin and as a reagent for nucleophilic B-C and B-B bond formation when treated with C-or B-centred electrophiles. [47][48][49] Although this is consistent with the generation of an intermediate boryl species, we have also observed that reaction of 9 with imines provides the N-B bonded organomagnesium compounds rather than the product of nucleophilic C-borylation (Scheme 1).…”
mentioning
confidence: 86%
“…50 In this case, B-B cleavage does not result in a terminal magnesium boryl species but occurs through attack of the imine nitrogen at the three-coordinate boron of the diboranate anion. 50 In contrast, treatment of 9 with 4-dimethylaminopyridine does provide the Mg-B bonded species, [(BDI)Mg(Bpin)DMAP] (10), 45,46 raising questions about the generality of such an 'outer sphere' process. In this contribution, we extend our study to the reaction of compound 9 with triphenylphosphine oxide and address the mechanism of the resultant B-B heterolysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Single-crystal X-ray diffraction analyses of 3-Mes ( Figure 2) and 3-Dur (see Figure S33 in the Supporting Information) confirmed their cationic 1,2-m-hydro-2aryltribora[3]ferrocenophane structures. [19] While there have been recent reports of linear B 3 H 6 À anions, [26] and of cyclic doubly base-stabilized B 3 H 6 + cations, [25] these are, to our knowledge, the first examples of linear triborane cations. As doubly base-stabilized analogues of the B 3 H 4 + cation they are also structurally related to the B 3 H 6 À anion, for which ab initio studies predict a similar C 1 symmetry, with a linear B 3 unit containing a m-bridging hydride as the structural minimum.…”
Section: Communicationsmentioning
confidence: 99%
“…Rçntgenstrukturanalysen geeigneter Einkristalle von 3-Mes (Abbildung 2) und 3-Dur (siehe Abbildung S33 in den Hintergrundinformationen) bestätigten die kationischen 1,2m-Hydro-2-Aryltribora[3]ferrocenophan-Strukturen. [19] Während kürzlich von linearen B 3 H 6 À -Anionen, [26] sowie von cyclischen, doppelt basenstabilisierten B 3 H 6 + -Kationen berichtet wurde, [25] handelt es sich bei den von uns präsentierten…”
Section: Zuschriftenunclassified